Biomedicine, deliberative democracy and childhood. The limits of children and young people’s involvement in health research - Murano, Maria Cristina (Las Torres de Lucca. International Journal of Political Philosophy, 2024)
In recent years, children and young people (CYP) have been increasingly included in patient and public involvement (PPI) in health research and innovation. Such initiatives intend to give a voice to CYP in such matters. Given that it is debated whether PPI in health care fosters the values of participation, public discussion and decision making put forward by deliberative democracy, this article examines three sets of challenges concerning the involvement of CYP by focusing on age biases. After describing some existing initiatives, the paper critically examines why CYP are involved, how the CYP group is constituted and then investigates the moral status of CYP in biomedical settings. It shows that the rationale for involving CYP in PPI is mainly top-down and adult-centric, thereby questioning the authentic participation in decision making. It also suggests that to ensure democratic inclusion, the CYP group should be constituted by considering both age and politics. Lastly, the article indicates that, despite the increasing recognition of child-specific rights, the sociocultural norms and power dynamics in pediatrics undermine their moral status and challenge political equality. These three sets of considerations offer a preliminary theoretical contribution toward improving democratic legitimacy and representation of CYP in health research and innovation.